Low radon exposure and mortality among Jouac uranium miners: an update of the French cohort (1946–2007). (6th December 2017) - Rage, Estelle; Caër-Lorho, Sylvaine; Laurier, Dominique
Abstract: After the extension of the French cohort of uranium miners with the inclusion of workers employed in the Jouac mines, this article seeks to describe the new Jouac cohort and to estimate mortality risks, as well as to quantify their relation to radon exposure in this extended cohort. The Jouac cohort includes 458 miners hired by the Société des Mines de Jouac between 1957 and 2001. There is no measurement of radon exposure before 1978 and so no data were available. Consequently, only the post-1977 Jouac cohort (n = 314) has been included in the French cohort, creating an extended cohort of 5400 French uranium miners followed up from 1946 to 2007. Mortality analyses computed the standardised mortality ratios (SMRs). Excess relative risks (ERRs) were assessed using Poisson regression models. No evidence of a significant excess risk of overall mortality (n = 66, SMR = 0.93; 95% CI = 0.72–1.19) or any specific mortality was observed in the Jouac cohort. In the extended cohort, overall mortality did not increase, but a significant excess of deaths was observed for all cancers (SMR = 1.11, 95% CI = 1.03–1.19), lung cancer (SMR = 1.32, 95% CI = 1.14–1.51), and kidney cancer (SMR = 1.58, 95% CI = 1.01–2.35). Cumulative exposure to radon was 3.9 working level month (WLM) and 35.1 WLM in the post-1977 Jouac and extended cohorts, respectively. Cumulative radon exposure was significantly associated with an excess risk of death from lung cancer (ERR/100 WLM = 0.73, 95% CI = 0.32–1.33) and from cerebrovascular diseases (ERR/100 WLM = 0.42 95% CI = 0.04–1.04). In conclusion, the Jouac cohort is still a young cohort and its inclusion leads to slight modifications compared to previous analyses of the French cohort. The already known relation between radon exposure and lung cancer death as well as the excess risk of death from cerebrovascular diseases persisted in the extended cohort.